Codification of Islamic law in the Muslim world: political intricacy and professional egoism - Zakariyah, Luqman (2013)
In the last century, the claim that the idea of codification of Islamic law is foreign, innovative and meant to undermine the divinity of the Islamic law is spurred by some Muslim jurists among are the members of the Saudi Arabia Council of Senior Scholars (ayhatkibar al-Ulama Al-su’udiyyah).But historically, literatures of Islamic legal theory reveal that the idea of codification of law as deemed in the West is very close to the idea of codification of Islamic legal maxims (taqnin al-qawaid al-fiqhiyyah) which unofficially emerged in Islamic jurisprudence as earlier as 1st century of Islamic law.This paper aims to explore the historical concept of the codification of Islamic law with focus on political desideratum surrounding the call for and against the concept of codification of Islamic law in Saudi Arabia with reference to other Muslim countries. I suggest the concepts of maslahah (public interest) and talfiq al-madhaahib(hybridization of schools of jurisprudence) as justificationsfor the realization of the benefit of the concept. In order to preserve the sacred nature of Shariah while codifying its laws, the concepts of textuality and intertextuality as working mechanisms are also proposed. The paper concludes that the codification of Islamic law through these mechanisms can remove ambiguities and fears being expressed about the possibility of codification of Shariah law and at the same time ensure justice in application of Islamic law our contemporary world.